Synthesis and Optical Properties of a Novel Hybrid Nanosystem Based on Covalently Modified nsio2 Nanoparticles with a Curcuminoid Molecule - Aravena-Ponce, D; Aravena-Ponce, D (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
A new curcuminoid molecule (3) has been designed and synthesized, containing a central -(CH2)2-COOH chain at the α carbon of the keto-enol moiety in the structure. The carboxylic acid group is added to react with exposed amino groups on silica oxide nanoparticles (nSiO2), forming an amide bond to attach the curcuminoid moiety to the nSiO2 covalently. The Kaiser test quantifies the functionalization degree, yielding 222 μmol of curcuminoid per gram of nanoparticles. The synthesized hybrid nanosystem, nSiO2-NHCO-CCM, displays significant emission properties, with a maximum emission at 538 nm in dichloromethane, similar to curcuminoid 1 (without the central chain), which emits at 565 nm in the same solvent. Solvent-induced spectral effects on the absorption and emission bands of the new hybrid nanosystem are confirmed, similar to those observed for the free curcuminoid (1). The new nanosystem is evaluated in the presence of kerosene in water, showing an emission band at 525 nm as a detection response. The ability of nSiO2-NHCO-CCM to change its fluorescence when interacting with kerosene in water is notable, as it overcomes the limitation caused by the insolubility of free curcuminoid 1 in water, allowing for the exploitation of its properties when connected to the water-stable nanosystem for future detection studies. © 2024 by the authors.